Chemical composition and distribution of dry matter in genotypes of banana and plantain fruits (2016)
The distribution of dry matter in the bunch and chemical attributes of the fruit were evaluated in 12 cultivars of plantain and banana from the Musaceae Colombian Collection (CCM) and the similarities among the clusters were determined by a statistical analysis of main components and conglomerates The variables percentages of matter in pulp, percentages of matter in nuts, percentages of fresh pulp, starch content, K, Ca, Cu, Mn, total sugars, ash, Fe, Zn, and Cu represented the greatest differentiation of the cultivars. Cultivars Orishelle (group 1) and FHIA-1 (group 2) had the highest levels of the minerals vFe and Zn; Orishelle, is an important source of minerals for human nutrition in general given its high content of Fe (51.7 ppm), which is above the overall average of the other cultivars evaluated (29.1 ppm), whereas higher levels of total sugars were found in the hybrid FHIA-21 (group 2) and cultivar Gross Michel coco (subgroup 3B). With a value of 83 % for the material, Pisang Mas (subgroup 3B), followed by Africa 1 (subgroup 3A) with 82.6 % and Gross Michel coco with 82.1 %, showed the highest percentages of matter in pulp with respect to the total per bunch. The cultivars Cachaco (group 2) and Dominico (subgroup 3A) had the highest percentages of fresh nuts per cluster.